Role of Extended White Blood Cell Parameters in Distinguishing Acute Febrile Illnesses - Tandry Meriyanti; Maroloan Aruan; Glorya N. D. Ananda (Advances in Hematology)
Conclusion: HFLC was a useful diagnostic tool to identify viral infection, particularly dengue infection, while IG, NLR, NE-SFL, and NE-WY can be useful to differentiate bacteremia from other acute febrile illnesses.